Dialectics, asking and escape: About Blanchot’s The Deepest Question - Salinas, Francisco (Re-presentaciones: Periodismo, comunicación y sociedad, 2020)
This brief text reflects on “the deepest question”, writing from L’ Entretien infini by Maurice Blanchot were the author asks questions about asking questions. Particularly, here I focus in one specific passage of the text where Blanchot uses the deepest question to elaborate connexions with dialectics (escape from monologs and systematized dialogues), the problem of asking it (impossibility of clarifying the question) and requirement of escaping (constant update of its flight). Here I propose to read and elaborate around this excerpt in consideration of the three aforementioned lines and raise some questions about our own times.
Keywords: Blanchot; questioning; dialectics; asking; scape